Antibacterial and antifungal activities of the polyphenolic fractions isolated from the seed coat of Abrus precatorius and Caesalpinia crista. Issue 23 (2nd December 2018) - Mobin, Lubna; Saeed, Syed Asad; Ali, Rashida; Saeed, Syed Ghufran; Ahmed, Rahil
Abstract: Crude seed coat extracts from Abrus precatorius and Caesalpinia crista were purified into four different fractions namely phenolic acids, flavonols, flavanols and anthocyanin which were then examined for their polyphenol contents and antimicrobial potentials. The fractions derived from seed coat of A. precatorius were found more potent with high phenolic and flavonoid contents as compared to C. crista fractions. The significant antibacterial activity was observed against all strain tested by the fractions of both samples apart from anthocyanin fraction. It was interesting to note that the phenolic acid fractions of both samples was found more active against gram-negative bacteria, while gram-positive bacteria were found to be more sensitive towards flavonol fractions. The phenolic acid and flavonol fractions being potent antibacterial were selected to demonstrate the antifungal capacity of two samples. Among them, phenolic acid fraction of both samples was found active towards all the fungal strain. Abstract :